DO KNOWLEDGE SHARING AND INFORMATION TECHNOLOGY MEDIATE THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE CREATIVITY? - Siti Nur Azizah; Much. Riyadus Solichin; Ika Susilowati (Media Bina Ilmiah, 2025)
This research aims to examine the effect of transformational leadership style on employee creativity by mediating the role of knowledge sharing and information technology in microfinance institutions in Central Java. The population of this study was all employees of micro-financial institutions in Central Java, and the sample used was 250 employees who were selected using a non-probability sampling technique with purposive sampling, namely employees in marketing, administration and services, information and Information Technology departments who had worked for at least 1 year. Data were analyzed using SEM with the help of PLS ​​3. This research proves that transformational leadership adopted by microfinance institutions can increase employee creativity. Likewise, with the mediation of information technology and the mediation of knowledge sharing, the influence of transformational leadership can boost employee creativity.